Polyurethane foams from liquefied orange peel wastes - Domingos, Idalina (2019)
Waste conversion into value added materials is a growing subject due to environmental concerns. In the production of orange juice high amounts of orange peel waste are generated and although they are used for the extraction of some extractable compounds a new waste is generated not much different from before. The aim of this work was to determine the possibility of efficiently converting orange peel waste into a liquefied material for the production of more environmentally benign polyurethane foams and test the influence of the proportion of isocyanate, catalyst, surfactant and blowing agent in physical and mechanical properties of the foams. Dry orange peel was liquefied using a mixture of ethyleneglycol and glycerol (1:1) as solvents, catalysed by sulphuric acid at 180 °C for 60 min. A ratio of 9:1 solvent/lignocellulosic material was used and 3% of sulphuric acid was added based on the solvent mass. Density, compressive stress at 10% and young modulus were determined for each foam. The results show that a good liquefaction yield can be achieved by polyalcohol liquefaction of orange peel waste and that this material can successfully be converted into a polyurethane foam with satisfying properties. Moreover the results showed that the physical and mechanical properties of the foam could be tailored by a careful choice of the additives used in foam formation